Proving The True Identity Of Evelyn Salt In The Phillip Noyce's Salt Movie (2010): A Psychoanalytic Approach - Ferdinanto, Tendika, Drs. Abdillah Nugroho, M.Hum, Drs. Sigit Haryanto, M.Hum (2013)
The problem of this research is "How is proving the true identity of Evelyn Salt reflected in Phillip Noyce's Salt Movie?". This research is aimed to analyze Phillip Noyce's Salt Movie based on the structural elements of movie and to describe proving the true identity of Evelyn Salt reflected in Phillip Noyce's Salt Movie using a Psychoanalytic Approach. This research is qualitative research. The object of the study is Salt movie directed by Phillip Noyce in 2010. The data are taken from Salt movie directed by Phillip Noyce and the script written by Kurt Wimmer and Brian Helgeland. The other data source is books and other sources that support the analysis. The data collection technique is watching the movie several times, reading the movie script, determining the character that analyzed, taking notes of important parts in both primary and secondary data, and classifying and determining the relevant data. The result of the study found that there is a relationship between Salt movie and psychoanalytic approach, first on the structural element of the movie; where the message to Salt movie shows that Evelyn Salt the major character who is accused of being a Russian sleeper agent and goes on the run to try to clear her name. the point of view is, the director wants to show the real life of people in Palestine against Israel. The theme of the movie is 'The hard tries to get a huge purpose'. The true identity of Salt related with psychoanalytic approach is that the hate, fear, and loyal of Salt makes him brave to change her identity from the spy into the a hero who defense the America from the betrayer.